A PROSPECTIVE OBSERVATION STUDY ON PRE-FIXATION COMPRESSION SCREW AS AN INNOVATIVE METHOD FOR VARUS CORRECTION IN PROXIMAL FEMORAL NAILING FOR INTERTROCHANTERIC FRACTURES: A RANDOMIZED CONTROLLED TRIAL - Mishra, Abhisek; Mohanty, Tanmoy; Mishra, Sudarshana (Student's Journal of Health Research Africa, 2025)
Background Femur intertrochanteric fractures (IT) are frequent in the elderly population. For this age range, internal fixation using a minimally invasive technique would be optimal to lower morbidity. Objectives The purpose of this study is to assess the results and efficacy of varus alteration with a pre-fixation compression screw in the proximal femoral nailing of intertrochanteric fractures. Materials and methods This prospective observation study was conducted at a tertiary health care centre. The study was conducted for two years (January 2022 to January 2024). A total of hundred patients were enrolled in this study. The study will enroll patients aged 50 years and older who present with intertrochanteric fractures and are indicated for surgical treatment. Results The demographic analysis showed no significant differences in gender distribution, side of injury, or fracture type between PFN patients with and without PFCS. However, patients without PFCS were significantly older than those with PFCS (p<0.001). The intervention group, i.e., PFN with PFCS, showed significantly better outcomes in terms of fracture alignment and functional recovery. All the parameters, including alignment, Harris hip score, fracture union, length of stays, and complications, were found to be statistically significant (p-value <0.001) between PFN with PFCS group and PFN without PFCS. Conclusion The use of a PFCS in combination with PFN for the surgical treatment of intertrochanteric fractures had significant benefits, according to this study. Specifically, improved fracture alignment, improved functional recovery, and fewer postoperative issues have resulted from the use of PFCS. Recommendation The study recommends the use of a pre-fixation compression screw (PFCS) with proximal femoral nailing (PFN) for intertrochanteric fractures to enhance fracture alignment and functional recovery while reducing postoperative complications.